2005
DOI: 10.1007/s00027-005-0788-z
|View full text |Cite
|
Sign up to set email alerts
|

Periphyton metabolism along a nutrient gradient in a desert river (Truckee River, Nevada, USA)

Abstract: Abstract. Periphyton metabolism was studied at fi ve sites along a 70 km unshaded stretch of the Truckee

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
(60 reference statements)
2
7
1
1
Order By: Relevance
“…For example, Naegeli and Uehlinger (1997) Here we have simply ascribed the consumption of oxygen to respiration, as is common in the literature, whereas it obviously includes the oxidation of methane, ammonia, and other reduced substrates. Our instantaneous rates of GPP (a simple sum of P and R per hour scaled to one day) of 1.2-3.4 g O 2 m 22 d 21 are also comparable to those measured for periphyton growing on artificial tiles (3.3-9.1 g O 2 m 22 d 21 ; Uehlinger and Brock 2005). Clearly, therefore, there is great potential for epilithic primary production on the gravels to add to the already substantial productivity of the Ranunculus spp.…”
Section: Discussionsupporting
confidence: 80%
“…For example, Naegeli and Uehlinger (1997) Here we have simply ascribed the consumption of oxygen to respiration, as is common in the literature, whereas it obviously includes the oxidation of methane, ammonia, and other reduced substrates. Our instantaneous rates of GPP (a simple sum of P and R per hour scaled to one day) of 1.2-3.4 g O 2 m 22 d 21 are also comparable to those measured for periphyton growing on artificial tiles (3.3-9.1 g O 2 m 22 d 21 ; Uehlinger and Brock 2005). Clearly, therefore, there is great potential for epilithic primary production on the gravels to add to the already substantial productivity of the Ranunculus spp.…”
Section: Discussionsupporting
confidence: 80%
“…GPP rates in this study (0 to 8.4 g O 2 m −2 day −1 ) were comparable to rates measured in other streams having varying levels of basin disturbance (Hall 1972;Bott et al 1985;Young and Huryn 1996;Mulholland et al 2001;Uehlinger and Brock 2005) and below some of the values reported for similar prairie/agriculture land use (<0.1 to >50 g O 2 m −2 day −1 , Wiley et al 1990). CR-24 rates generally were greater than those measured in investigations by Hall (1972), Hall and Tank (2003), and Mulholland et al (2001), which ranged from 0.4 to 13 g O 2 m −2 day −1 but were comparable to, and in some cases lower than, rates reported in the literature for similarly disturbed systems (Wiley et al 1990;Houser and Mulholland 2005).…”
Section: Nutrient and Algal Measures As Related To Stream Metabolism supporting
confidence: 83%
“…Past research has shown that physical factors, such as light availability, temperature, and channel/habitat characteristics (Bott et al 1985(Bott et al , 2006Wiley et al 1990;Ortiz-Zayas et al 2005;Uehlinger and Brock 2005), can significantly influence production and respiration.…”
Section: Selected Environmental Variables Related To Stream Metabolismentioning
confidence: 99%
See 1 more Smart Citation
“…Periphytic algae are believed to be the major primary producers in headwater and midregion areas of river systems, but there have been relatively few studies of algal PP in streams on an annual basis (Fuller and Bucher 1991;Uehlenger 2006). Primary productivity in flowing water systems is estimated from oxygen change or carbon dioxide change in open stream (Uehlenger 2006;Bott et al 2006), or is measured in closed chambers placed in laboratory or in situ (Munn and Brusven 2004;Uehlinger and Brock 2005;Reid et al 2006) by 14 C uptake (Ostrofsky et al 1998), or by using O 2 microelectrode (Dodds et al 1999). PP can also be calculated from chlorophyll a (algae biomass) estimations (Fellows et al 2006).…”
Section: Introductionmentioning
confidence: 99%